Analysis of Microstructure and Performance of Laser Cladding WC-Fe316L Alloy on the Surface of 27SiMn Steel. Issue 1 (1st January 2022) - Li, Chuanzhu; Ni, Yuji; Wang, Mingdi; Lu, Zheng; Zhang, Pengcheng
Abstract: In order to solve the problem that the hydraulic support column is affected by the sulfur and chlorine water vapor in the mine, the inner wall will inevitably have different forms of defects, such as surface wear and surface corrosion. The pure Fe316L cladding layer and the WC-Fe316L composite cladding layer with the hard phase WC mass fractions of 10%, 20%, and 30% were prepared on the 27SiMn steel substrate for hydraulic support column by homogenizing broadband laser head. The phase composition, microstructure, microhardness and wear resistance of four cladding samples were studied. The results show that the pure Fe316L cladding layer forms a good metallurgical bond with the substrat, the surface of the cladding layer has no crack defects, and the shape is good. The average microhardness of the pure Fe316L cladding layer is increased by 1.4 times compared with the 27SiMn steel base, and it is increased to 331.2HV0.5. At the same time, the wear rate of the pure Fe316L cladding layer is reduced by 30.8% compared with that of the matrix. The mass fraction of WC particles is 10 %, 20%, and 30% of the WC-Fe316L cladding layer's microhardness is 1.6, 1.7 and 2.0 times higher than that of the 27SiMn steel matrix to 369.9HV0.5, 408.6HV0.5 and 481.6HV0.5, and each WC The wear rate of Fe316L composite cladding layer was reduced by 45.8%, 66.0% and 82.3% compared with the matri composite cladding layer. The addition of WC particles helps to strengthen the solid solution strengthening and fine-grain strengthening of the composite cladding layer, and the unmelted WC particles also strengthen the dispersion strengthening effect of the composite cladding layer.